2020
DOI: 10.1016/j.infsof.2020.106274
|View full text |Cite
|
Sign up to set email alerts
|

Is this GitHub project maintained? Measuring the level of maintenance activity of open-source projects

Abstract: Context: GitHub hosts an impressive number of high-quality OSS projects. However, selecting "the right tool for the job" is a challenging task, because we do not have precise information about those high-quality projects. Objective: In this paper, we propose a data-driven approach to measure the level of maintenance activity of GitHub projects. Our goal is to alert users about the risks of using unmaintained projects and possibly motivate other developers to assume the maintenance of such projects. Method: We … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0
12

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 45 publications
0
38
0
12
Order By: Relevance
“…Although these metrics do not necessarily reflect software quality, Coleman et al [11] demonstrated that quantitative metrics such as lines of code can be useful in evaluating software maintainability. Similarly, a recent study [7] showed that such code commit-related attributes can be used to evaluate the maintenance level of open-source projects.…”
Section: Code Maintenance Activities Analysismentioning
confidence: 99%
“…Although these metrics do not necessarily reflect software quality, Coleman et al [11] demonstrated that quantitative metrics such as lines of code can be useful in evaluating software maintainability. Similarly, a recent study [7] showed that such code commit-related attributes can be used to evaluate the maintenance level of open-source projects.…”
Section: Code Maintenance Activities Analysismentioning
confidence: 99%
“…This adaptability is conducive to collaboration, the creation of mutually supportive user/developer communities and rapid evolution, making open source software ecosystems fast moving and highly diverse. It is impossible to discuss all software options that could be used for geographic transport planning: there are literally thousands of software projects written in dozens of programming languages, many of which are no longer actively maintained (Coelho et al 2020). Transport planners should use solutions that are future proof and actively maintained.…”
Section: Defining Open Sourcementioning
confidence: 99%
“…Las técnicas utilizadas para clasificar los repositorios son Random Forest y Naive Bayes. De la misma forma, en Jiang et al ( 2021) y Coelho et al (2020) se aplican técnicas de machine learning basadas en redes neuronales para hacer recomendación de repositorios a partir de las etiquetas que contienen elementos del repositorio, tales como code, title, commits. Siguiendo en la misma línea, en Kallis, Di Sorbo, Canfora y Panichella (2020) se propone Ticket Tagger, una aplicación de GitHub que analiza el título y la descripción del repositorio mediante técnicas de machine learning para reconocer automáticamente los tipos de informes enviados en GitHub y asignar etiquetas a cada repositorio en consecuencia, aplicando algoritmos de clasificación de texto basados en clasificadores lineales, además de un enfoque de Deep Learning usando redes neuronales.…”
Section: Trabajos Relacionadosunclassified